Resolução de conflitos ambientais no Brasil: do patriarcal ao fraternal - Paulo Renato Ernandorena (Estudios Sociales)
This study, holding as background the conflicts that involve the environment, analyzes the fraternity principle, from the perspective of the theory proposed by Baggio, 2 concluding that the official pattern of environmental litigations composition that exist in Brazil -solidified by the obsolete monopoly of Judiciary- consolidated on a Law's positivism and on a competitive point of view of the society, does not contemplates the fraternity as a legal value. In other hands, the paper starts to focus the mediation, making clear that this alternative way of contest's solution not only disposes with justness to the environmental conflicted issue but -remarkably by its communicative characteristic acting and shared true- deeply excited by the fraternity idea. The subject has been researched in the specialized literature, making sure about the precarious systematization of the mediation as management way of environmental conflicts, as well as a lack on the approach of the fraternity as juridical category of potential incidence at the environmental field. In the end, the analysis concludes that the eco mediation may appease the insertion of the fraternity component on arguing related to environmental estates, generally ruled by the radicalization and a vision of world's representationalism, contributing perhaps to the co-operation construction of a new paradigmatical systemic epistemology for conflicts solutions, that insures the emphasized roll to fraternal as imperative of conduct.